The impact of remittances on GDP in CARICOM - Millington, Faith W E (GSB: Faculty, 2016)
This study investigates the relationship between remittances and economic growth in the Caribbean Community (CARICOM) from 1975 to 2013, where remittances are measured as a share of GDP and economic growth is measured by GDP per capita growth. Using multivariate linear regression analysis and the Generalised Method of Moments (GMM) the researcher tested the hypothesis that remittances have a positive relationship on GDP per capita growth within CARICOM. Additionally, the ability of financial development to influence the relationship between remittances and GDP per capita growth was also tested. In this study financial development was measured using the proxy variables of quasi money, M2 and banking credit to the private sector. The relationship between remittances and economic growth has been shown to vary across countries and regions. In this study it was found that remittances as a share of GDP growth do not have an overall statistically significant influence on GDP per capita growth but do effect GDP per capita growth through their interactions with inflation and banking credit to the private sector.